Nipisat - a Saqqaq culture site in Sisimiut, central West Greenland (Vol. 331) - Gotfredsen, Anne Birgitte (Monographs on Greenland | Meddelelser om Grønland, 2004)
d on immature individuals caught primarilyduring their first summer on the breeding grounds. The inhabitants at Nipisat alsohunted caribou on the mainland. The age structure and sex distribution of the caribouremains primarily reflect stalking. Selected body parts, especially the fore and hind legsand the heads, were transported to the island for raw material, meat filleting and furtherprocessing for marrow extraction and fat rendering. The exploitation of fauna through the entire occupation period was remarkablyconstant with respect to choice of game animal and the selected age groups. Althougheiders were more abundant in phase 1 (36%) than in phase 3 (17%) while gulls increasedfrom 43 to 61% in the same time period. The same trend was found valid for geese, whichincreased over time while the importance of auks decreased. Harbour porpoise seem tohave decreased while walrus increased in relative importance through time. Caribouseem to be of greater importance in phase 3 with 55% compared to 45% in phase 1. Theslight shift in preferred resources may be explained by fluctuating abundance and availabilityof the game species combined with the development of new hunting tools. Based on the new investigations in the Sisimiut District, the gap between Saqqaqand Dorset Culture in Central West Greenland has been diminished. Although resourceexploitation at the site seems to have been very stable through all three phases, there areaspects of cultural change bridging the transition from Saqqaq to Dorset Cultures. Theintroduction of bevelled tools, sturdy harpoon or lance heads and the abandonment ofthe bow and arrow in phase 3, show cultural affiliation with Dorset technology. This isalso true in terms of lithic raw material preference, the introduction of soapstone artefactsand the absence of dwelling structures with a well-defined box-hearth. At the sametime it looks like, the central occupation area for the Saqqaq Culture shifted southwardsfrom the Qeqertarsuup Tunua area towards Sisimiut and Nuuk.